(untitled) (Circe de clásicos y modernos, 2018)
Far from the interpretation of Leon Battista Alberti as a prototype of the “universal man”, GARIN has analyzed the contradictory nature of Alberti’s thought. In fact, in the exten-sive and versatile work of the Genoese humanist two opposite visions of man and the world coexist: one believes in the power of reason, the other acknowledges the absurdity of life. It is in Momus and the Intercenales that this “somber Alberti” is present. In these texts the appeal to a simulated life is addressed through a form of laughter that demystifies the human ideal of the early Italian Renaissance.